Ecological limits of development living with the sustainable development goals - Kish, Kaitlin; Quilley, Stephen (Routledge studies in sustainable development, 2022)
"Embracing the reality of biophysical limits to growth, this volume uses the technical tools from ecological economics to re-cast the Sustainable Development Goals (SDGs) as Ecological Livelihood Goals - policy agendas and trajectories that seek to reconcile the social and spatial mobility and liberty of individuals, with both material security and ecological integrity. Since the 1970s, mainstream approaches to sustainable development have sought to reconcile ecological constraints with modernization through much vaunted and seldom demonstrated strategies of 'decoupling' and 'dematerialization.' In this context, the UN Sustainable Development Goals (SDGs) have become the orchestrating drivers of sustainability governance. However, biophysical limits are not so easily side-stepped. Building on an ecological-economic critique of mainstream economics, and a historical-sociological understanding of state-formation, this book explores the implications of ecological limits for modern progressive politics. Each chapter outlines leverage points for municipal engagement in local and regional contexts. Systems theory and community development perspectives are used to explore under-appreciated avenues for the kind of social and cultural change that would be necessary for any accommodation between modernity and ecological limits. Drawing on ideas from H.T Odum, Herman Daly, Zigmunt Bauman, and many others, this book provides guiding research for a convergence between North and South that is bottom up, household-centred, and predicated on a re-emerging domain of Livelihood. In each chapter, the authors provide recommendations for reconfiguring the UN's SDGs as Ecological Livelihood Goals - a framework for sustainable development in an era of limits. This book will be of great interest to students and scholars of ecological economics, socio-ecological systems, political economy, international and community development, global governance, and sustainable development"--Provided by publisher.